1992
DOI: 10.4319/lo.1992.37.7.1543
|View full text |Cite
|
Sign up to set email alerts
|

The role of food patches in maintaining high deep‐sea diversity: Field experiments with hydrodynamically unbiased colonization trays

Abstract: To test whether deep‐sea macrofaunal diversity is enhanced by specialization on small‐scale food patches, we deployed colonization trays by submersible at 900‐m depth for 23 d. Trays were buried flush with the seafloor to minimize potential hydrodynamic bias. Treatments included prefrozen, natural sediment that was unenriched or enriched with either Thalassiosira sp. or Sargassum sp. Density comparisons and rarefaction analysis indicate that Thalassiosira sp. attracted high densities of several taxa of juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 5 publications
2
63
1
Order By: Relevance
“…Colonization experiments in the low-oxygen Santa Catalina Basin also yielded assemblages containing a significant proportion of ambient fauna (Levin and Smith, 1984). In contrast, early colonization tray experiments in the Atlantic revealed abundant, opportunistic colonizers that were often rare in ambient sediments (Desbruyères et al, 1980;Grassle and Morse-Porteous, 1987;Snelgrove et al, 1992). These included capitellid, hesionid, dorvilleid, spionid, and sigalionid polychaetes, cumaceans and leptostracans.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Colonization experiments in the low-oxygen Santa Catalina Basin also yielded assemblages containing a significant proportion of ambient fauna (Levin and Smith, 1984). In contrast, early colonization tray experiments in the Atlantic revealed abundant, opportunistic colonizers that were often rare in ambient sediments (Desbruyères et al, 1980;Grassle and Morse-Porteous, 1987;Snelgrove et al, 1992). These included capitellid, hesionid, dorvilleid, spionid, and sigalionid polychaetes, cumaceans and leptostracans.…”
Section: Introductionmentioning
confidence: 99%
“…The type of food present also affected colonization. In the Atlantic, trays containing the diatom Thalassiosira attracted significantly more colonists than those containing the seaweed Sargassum (Snelgrove et al, 1992(Snelgrove et al, , 1994. On the Pakistan margin, consumers of phytodetritus varied as a function of oxygen regime (Woulds et al, 2007(Woulds et al, , 2009, with protists dominating phytodetritus consumption at O 2 concentrations below 0.1 mL L −1 (4 µM) and macrofauna dominating at slightly higher oxygen levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sediment percentage total organic carbon (%TOC) concentrations are the most widely available sedimentary parameter for representing the flux of particulate OM (POM) to the sea floor (Seiter et al 2004;2005), which exhibits significant regional variability (Lutz et al 2002). These concentrations can be a useful measure of resources available to support benthic biota (Snelgrove et al 1992) because positive relationships have been observed between %TOC and benthic biodiversity (Snelgrove and Butman 1994;Snelgrove et al 1996). %TOC is often inversely correlated with grain size (Mayer 1994;Keil et al 1997) because ,99% of sedimentary OM occurs in fine fractions as discontinuous blebs on clay surfaces (Ransom et al 1997).…”
Section: Introductionmentioning
confidence: 99%